Lip Lifting: Not Just Fullness—Everything You Need to Know about Lifting and Creating Youthful, Beautiful Lips - Spiegel, Jeffrey H.; Spiegel, Onir L. (Facial Plastic Surgery, 2019)
This article will explain the theories and practice of creating the most beautiful lips. This article also discusses lip lifting, lip augmentation, and lip injectables.
Keywords: lip lift; lip augmentation; lip injection